National data linkage assessment of live births and deaths in Mexico: estimating under-five mortality rate ratios for vulnerable newborns and trends from 2008 to 2019 - Suárez-Idueta, Lorena (2023)
Children's Investment Fund Foundation (United Kingdom). Wellcome Trust.